Diagnostic evaluation of appendiceal orifice inflammation in ulcerative colitis - Zhan, Da-Qin; Chen, Xing; Wang, Rong; Zhang, Jing; Zhao, Dan Yu; Zhang, Shu Jing; Wang, Zhi Feng; Ma, Rui Jun; Hou, Bo (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: To evaluate the diagnostic significance of appendiceal orifice inflammation (AOI) in ulcerative colitis (UC) patients. Materials and Methods: We retrospectively examined data from patients with colitis from May 2010 to January 2014 and assigned them to two groups: UC cases and specific colitis cases. First, we clarified the difference in the AOI+ rate between the two groups. Thereafter, imaging findings of all the patients with colitis were reexamined. Features of AOI alone or in combination with proctitis (referred to as “combination features”) were considered as the two separate diagnostic criteria for diagnosing UC. By comparing the current diagnoses with the previous diagnoses, evaluation indexes were obtained. Results: A total of 3582 colitis cases (UC cases: 427; specific colitis cases: 3155) were examined. The mean AOI+ rates in UC and specific colitis cases were 26.2% and 0.7%, respectively; a Chi-squared test indicated that the difference between these rates was statistically significant (x2=6.81; p<0.001, OR=50.99). When the AOI features alone were used to diagnose UC, the sensitivity was 26.2% [95% confidence interval (CI), 22.3%–30.6%], agreement rate was 90.6%, and specificity was 99.3% (95% CI, 98.9%–99.5%). When the combination features were used to diagnose UC, the sensitivity was 26.2% (95% CI, 22.3%–30.6%), agreement rate was 91.1%, and specificity was 99.9% (95% CI, 99.7%–100%). Conclusion: Combining AOI features and proctitis may lead to a more effective UC diagnosis and enable physiciansto identify this condition more promptly among miscellaneous diseases.